Continuity and renewal of Catholic liturgical music in the Congregation of the Sisters of St. Paul of Chartres, Philippine province (1935-2008) - Asencio, Sr. Ma. Theresa
This study examines how continuity and renewal are expressed in the music of the Sisters the liturgical reforms of the Second Vatican Council. In the context of the directive of Sacrosanctum Concilium to keep alive the church;s treasury of music some songs of the Sisters discussed the study incorporate elements of the Gregorian chant such as free rhythm, recitative,psalmodic styles and modes. Using Gregorian chant inspired music as anchor, the Sisters of St. Paul worked creatively to give birth to the adaptation of musical strategies of appropriation and localization of melodies, integration of lowland dance and folk-like music and rhythms evoking the festive, ethnic and kundiman styles of the Filipino. These are concrete manifestations of indegenization and renewed liturgical music, an innovation to the musical forms of the Second Vatican council.